Nanotechnology to Overcome Blood–Brain Barrier Permeability and Damage in Neurodegenerative Diseases - Adriana Jiménez; Enrique Estudillo; Mara A. Guzmán-Ruiz; Nieves Herrera-Mundo; Georgina Victoria-Acosta; Enoc Mariano Cortés-Malagón; Adolfo López-Ornelas (Pharmaceutics)
The blood–brain barrier (BBB) is a critical structure that maintains brain homeostasis by selectively regulating nutrient influx and waste efflux. Not surprisingly, it is often compromised in neurodegenerative diseases. In addition to its involvement in these pathologies, the BBB also represents a significant challenge for drug delivery into the central nervous system. Nanoparticles (NPs) have been widely explored as drug carriers capable of overcoming this barrier and effectively transporting therapies to the brain. However, their potential to directly address and ameliorate BBB dysfunction has received limited attention. In this review, we examine how NPs enhance drug delivery across the BBB to treat neurodegenerative diseases and explore emerging strategies to restore the integrity of this vital structure.